COST MANAGEMENT OF SUSTAINABLE DEVELOPMENT OF THE COASTAL AREA IN THE REPUBLIC OF CROATIA - Ivan Peronja (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The coast is spatially the most valuable region in the Republic of Croatia. The value and attractiveness of the space for life led to the region's devastation during the period when the protection of the environment and sustainable development were not very important topics. These are reasons why the costs of sustainable coastal development are higher than outside of the coastal region. The Republic of Croatia cannot pay them in the short term, but it has to resort to European and world funds and private investments. Total costs can be observed in the framework of recovery of the existing state, management, and investment. Management models in Croatian coastal counties are different, they are not adapted to the strategic commitment to sustainable development, and the annual cost management reports of the coastal area are not comparable. The coastal sustainable development cost types are not specific for the region, but the regime of costs is more rigid and expensive. The coastal sustainable development implementation is slow and difficult. Principally, the costs bear private investors, citizens, and the state. By using economic instruments, such as external costs internalization and fiscal policy, the state endeavors to stabilize the frame of sustainability and make it attractive for investments. The citizens bear a double burden, primarily when they pay the costs of the state within the budget, and secondary through growing prices and by losing jobs. These are the consequences of the sustainable development strategy in the short-term period when the costs to the environment are still higher than the benefits. The valuation of immeasurable cost is not as objective as it would be able to be, and such damage is mainly underestimated. Full objectiveness can discourage potential investors, especially at the beginning of a new strategy implementation. Restructuring the sustainable development of coastal tourism and investment in aquaculture and blue biotechnology is an opportunity for the coastal area of the Republic of Croatia in the long run. The benefit at the same time should not be exclusively measurable value.